General boundary conditions for a Dirac particle in a box - Alonso, Vidal; De Vincenzo, Salvatore (Ciencia)
The most general relativistic boundary conditions (BCs) for a “free” Dirac particle in a one-dimensional box are discussed. It is verified that in the Weyl representation there is only one family of BCs, labelled with four parameters. This family splits into three subfamilies in the Dirac representation. The energy eigenvalues as well as the corresponding non-relativistic limits of all these results are obtained.